2017
DOI: 10.1590/0034-7167-2016-0474
|View full text |Cite
|
Sign up to set email alerts
|

Elderly who take care of elderly: a study on the Frailty Syndrome

Abstract: Objective: Identifying prevalence of frailty in elderly caregivers inserted in a high social vulnerability context and its correlation with sociodemographic and health aspects. Method: Descriptive, correlational and cross-sectional study. Forty elderly caregivers were evaluated with: questionnaire for caregiver characterization, Mini Mental State Examination, Katz Index, Lawton instrumental activities of daily living scale, Geriatric Depression Scale and the frailty phenotype proposed by Fried. Interviews were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
2
20
1
3
Order By: Relevance
“…The prevalence of frailty in the elderly caregivers of the sample was 20.8%, higher than a study carried out with elderly caregivers inserted in a context of high social vulnerability (10%) (16) and the study conducted in an outpatient clinic (18%) (17) . A systematic review has shown that the prevalence of the syndrome in the Brazilian elderly can vary from 7% to 59%, depending on the place of study, the inclusion criteria of the participants and the size of the sample (26) , which makes it difficult to compare of data.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The prevalence of frailty in the elderly caregivers of the sample was 20.8%, higher than a study carried out with elderly caregivers inserted in a context of high social vulnerability (10%) (16) and the study conducted in an outpatient clinic (18%) (17) . A systematic review has shown that the prevalence of the syndrome in the Brazilian elderly can vary from 7% to 59%, depending on the place of study, the inclusion criteria of the participants and the size of the sample (26) , which makes it difficult to compare of data.…”
Section: Resultscontrasting
confidence: 57%
“…Currently, there are several studies related to the frailty syndrome in the elderly. When it comes to elderly caregivers, data are still scarce (16)(17) . In Brazil, a study carried out with 50 elderly caregivers of elderly people attended in an outpatient clinic identified that there is an association between depressive symptoms and frailty.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 32% of the caregivers were frail, and only 4% were robust, suggesting that they were not in much better condition physically to look after the care-recipients. In fact, our study had the highest proportion of frail caregivers in comparison with other studies which reported the proportion of frail caregivers ranged from 8%-17% (Dassel & Carr, 2014;Santos-Orlandi et al, 2017;Sugimoto et al, 2018). However, it may be inappropriate to compare results across studies because of the heterogeneity between the study populations and the different types of frailty assessment tools that were used.…”
Section: Factors Associated With the Four Types Of Caregiver Reactionsmentioning
confidence: 56%
“…There was a predominance of elderly people with low educational level, an indicator of risk to negatively impact the health of the elderly and cause adverse effects. Evidence indicates that low schooling may present mental health problems, chronic conditions and, consequently, be an end to frailty, in addition to social exclusion, less access to information and unfavorable socioeconomic conditions (5) .…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that the frailty can be aggravated by the absence of social support, since the lack of it can affect the body's defense systems, making the individual more susceptible to illness (5) . It is presumed that maintaining family support relationships and social relationships promotes better health conditions for the elderly, favoring resilience in cases of stressful situations (6) .…”
Section: Introductionmentioning
confidence: 99%